2008
DOI: 10.1248/cpb.56.150
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Metformin HCl 500 mg Sustained Release Matrix Tablets Using Artificial Neural Network (ANN) Based on Multilayer Perceptrons (MLP) Model

Abstract: The aim of the present study was to apply the simultaneous optimization method incorporating Artificial Neural Network (ANN) using Multi-layer Perceptron (MLP) model to the development of a metformin HCl 500 mg sustained release matrix tablets with an optimized in vitro release profile. The amounts of HPMC K15M and PVP K30 at three levels (؊1, 0, ؉1) for each were selected as casual factors. In vitro dissolution time profiles at four different sampling times (1 h, 2 h, 4 h and 8 h) were chosen as output variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
(34 reference statements)
0
12
0
1
Order By: Relevance
“…Tablets were evaluated for their characteristic parameters, such as weight variation, hardness, friability, thickness, disintegration time, drug content, in vitro dissolution study [8, 10, 11, 20] shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Tablets were evaluated for their characteristic parameters, such as weight variation, hardness, friability, thickness, disintegration time, drug content, in vitro dissolution study [8, 10, 11, 20] shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Administration of a sustained-release, once-a-day metformin dosage form could reduce the dosing frequency and improve patient compliance. [2] Sustained or controlled drug delivery occurs when embedded within a polymer that may be natural or semi-synthetic or synthetic in nature. The polymer is judiciously combined with the drug or other active ingredients in such a way that the active agent is released from the material in a predetermined fashion and releases the drug at a constant rate for the desired time period.…”
Section: Introductionmentioning
confidence: 99%
“…SR products are needed for metformin to prolong its duration of action and to improve patient compliance. [3]…”
Section: Introductionmentioning
confidence: 99%